Examining the relationship between fatigue and cognition after stroke: a systematic review - Lagogianni, Christodouli; Thomas, Shirley A.; Lincoln, Nadina (Taylor & Francis, 2016)
Many stroke survivors experience fatigue, which is associated with a variety of factors including cognitive impairment. A few studies have examined the relationship between fatigue and cognition and have obtained conflicting results. The aim of the current study was to review the literature on the relationship between fatigue and cognition post-stroke. The following databases were searched: EMBASE (1980–February, 2014), PsycInfo (1806–February, 2014), CINAHL (1937–February, 2014), MEDLINE (1946–February, 2014), Ethos (1600–February, 2014) and DART (1999–February, 2014). Reference lists of relevant papers were screened and the citation indices of the included papers were searched using Web of Science. Studies were considered if they were on adult stroke patients and assessed the following: fatigue with quantitative measurements (≥ 3 response categories), cognition using objective measurements, and the relationship between fatigue and cognition. Overall, 413 papers were identified, of which 11 were included. Four studies found significant correlations between fatigue and memory, attention, speed of information processing and reading speed (r = −.36 to .46) whereas seven studies did not. Most studies had limitations; quality scores ranged from 9 to 14 on the Critical Appraisal Skills Programme Checklists. There was insufficient evidence to support or refute a relationship between fatigue and cognition post-stroke. More robust studies are needed.